Seasonal Differences in the Cost and Engagement of Facebook Advertisements for a Physical Activity Smartphone App. Issue 6 (July 2021) - Northcott, Celine; Curtis, Rachel; Bogomolova, Svetlana; Olds, Timothy; Vandelanotte, Corneel; Plotnikoff, Ronald; Maher, Carol
Purpose: To evaluate the performance of Facebook advertisements for a physical activity smartphone app at different times of the year. Design: A repeated cross-sectional study examined the cost and engagement levels of advertisements during 3 time points: Post-Easter April-May 2019, Pre-Summer October 2019, and New Year January 2020 . Setting: Advertisements were delivered on Facebook. Subjects: The target population was Australian females aged 25-60 years. Measures: Cost was evaluated in terms of reach per dollar. Engagement was evaluated in terms of click-through and app downloads per reach. Analysis: ANOVA and Chi-square were used to assess differences in reach per dollar, click-through, and app downloads per reach between time points. Results: Reach per dollar was highest in Post-Easter, but declined in Pre-Summer and New Year (reach/ 34.8 vs 31.5 vs 27.5; p = .004). Click-through was highest in New Year followed by Post-Easter, then Pre-Summer (click-through 3.2% vs 1.9% vs 1.2%; p < .001). New Year and Post-Easter advertisements achieved higher app downloads per reach than Pre-Summer (downloads 0.9% vs 0.7% vs 0.3%; p < .001). Conclusion: Facebook advertisements were cheaper in the first time-point, and appear to be getting more expensive (i.e. declining reach/). Advertisements in the New Year achieved the highest click-through and app downloads per reach, suggesting a useful time of year to promote physical activity products.